Varya's Individual Confrontation with Grief and Mortality in Chloe Benjamin's The Immortalists - Irfansyah, M. Ardy Noor; Marsih, Linusia (CV. Era Digital Nusantara, 2025)
Death and grief, while universally experienced, manifest in profoundly different ways across individuals, shaped by personal history, psychological makeup, and existential circumstance. Literature has long served as a powerful medium for examining these individual differences in confronting mortality, offering readers an intimate lens into the diverse human responses to loss. Through this study, titled